REDUCING STUDENT’S DISRUPTIVE BEHAVIORS USING STICKY FLASHCARD - Husain, Nurul Kamilati; Sada, Clarry; ., Ikhsanudin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The students of the third grade of SDS Al-Madani Pontianak performs disruptive behavior and their mean score is low. For that, the researcher uses sticky flashcard as a media in teaching English. The research aimed to investigate the use of sticky flashcard to reduce the students’ disruptive behavior, to improve students’ vocabulary score and students’ response using sticky flashcard. The researcher conducts a classroom action research in two cycles. The observation checklist, field notes, written tests and questionnaire are used to collect the data. First cycle, sticky flashcard uses through discussion, the result 32 disruptive behaviors occurs and the mean score is 54. Second cycle, sticky flashcard uses through games, the result 3 disruptive behaviors occurs and the mean score is 76. The students’ response are excited and helped by sticky flashcard. The conclusion, the use of sticky flashcard reduces the students’ disruptive behavior and improves the students' vocabulary achievement. Keywords: Sticky Flashcard, disruptive behaviors, vocabulary. Abstrak: Siswa kelas tiga SDS Al-Madani Pontianak seringkali menunjukkan sikap disruptif dan nilai rata-rata kosakata mereka rendah. Oleh karena itu, peneliti menggunakan sticky flashcard sebagai media pembelajaran dalam mengajar. Tujuan dari penelitian ini adalah untuk mengetahui penggunaan sticky flashcard dalam mengurangi sikap disruptif, meningkatkan nilai kosakata dan respon siswa terhadap sticky flashcard. Dalam penelitian ini, peneliti menggunakan penelitian tindakan kelas yang dilaksanakan sebanyak dua siklus. Dalam penelitian ini data didapatkan dari observasi checklist, field notes, test tulis dan kuisioner. Pada siklus pertama, peneliti menggunakan sticky flashcard melalui diskusi dan hasilnya terjadi 32 sikap disruptif dan nilai rata-rata siswa adalah 54. Pada siklus kedua, peneliti menggunakan sticky flashcard melalui permainan dan hasilnya terjadi 3 sikap disruptive dan nilai rata-rata siswa adalah 76. Siswa merespon dengan baik dan terbantu dengan sticky flashcard. Kesimpulannya adalah penggunaan sticky flashcard dapat mengurangi sikap disruptif dan meningkatkan nilai vocabulary siswa. Kata Kunci: Sticky Flashcard, sikap disruptif, kosakata.